Environment Approach on Optimizing Tourism Facilities at Tourism Village in Indonesia - Ginting, Nurlisa; Halim, Satria (Environment-Behaviour Proceedings Journal, 2019)
Tourism is a sector that always has a dynamic movement which will benefit the local community. Lumban Suhi-suhi is a tourist village famous for its ulos on Samosir Island that has become one of the tourist attraction. Due to the limitations of facilities arrangement make it becomes less of the attraction itself. Therefore, the environment-based mechanism becomes one of the concepts that will be applied to improve the tourist facilities in which could increase tourists in that area. The researcher uses a qualitative method in the form of direct observation and interview and analyzing data with related theory. Keywords: Tourism Village; Facilities; Sustainable Tourism; Environment eISSN: 2398-4287Â© 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i10.1617